An Error Analysis of Descriptive Text Written by Junior High School Students in Surakarta - Yuliani, Siti (JoLLIET, 2015)
The study deals with the error analysis in writing descriptive text for Junior High School students. The method of this research is descriptive quantitative. This research was carried out at SMP Islam Diponegoro, Surakarta. There are two techniques to collect the data, survey and test. The technique to analyze the data used in this research is error analysis. The steps of analyzing data started from collecting the data, identifying the error, describing the error, explaining the error, and drawing the conclusion.The result of this research are article errors were the highest number of linguistic errors with 49 errors or 45,37% and omission errors were the highest number of surfaceÂ  errors with 83 errors or 76,85%